Development and validation of prognostic nomogram for overall survival in canine multicentric lymphoma: a retrospective study - Zeyun Zhu; Zixiang Lin; Jun Dong; Di Zhang (BMC Veterinary Research)
Abstract This study aimed to develop and validate prognostic nomogram for predicting 3-month, 6-month, and 12-month overall survival in canine multicentric lymphoma. A total of 163 cases from January 2019 to December 2024 were used as a training set, and 50 cases from January 2017 to January 2019 served as a validation set. Predictors were identified using LASSO regression and univariate/multivariate Cox regression analyses, leading to the development of the nomogram: ATRAS2, incorporating age, red blood cell count at diagnosis, changes in red blood cell count after chemotherapy, and albumin-to-globulin ratio. Internal validation showed areas under the receiver operating characteristic curve for ATRAS2 of 0.991, 0.932, and 0.919 for 3-month, 6-month, and 1-year overall survival, respectively. Temporal validation yielded concordance indices of 0.708, 0.701 and 0.783 for 3-month, 6-month, and 1-year overall survival with calibration plots demonstrating strong agreement between predicted and observed overall survival. Decision curve analysis further confirmed the clinical utility of both models for 3-month, 6-month, and 12-month overall survival. The nomogram offers a tool for personalized survival evaluation of canine multicentric lymphoma.